Medial Temporal Lobe Subregional Atrophy in Aging and Alzheimer's Disease: A Longitudinal Study - Chauveau, Léa; Kuhn, Elizabeth; Palix, Cassandre; Felisatti, Francesca; Ourry, Valentin; de La Sayette, Vincent; Chételat, Gaël; de Flores, Robin (Frontiers in Aging Neuroscience, 2021)
Medial temporal lobe (MTL) atrophy is a key feature of Alzheimer’s disease (AD) but also occurs in typical aging. To enhance the clinical utility of this biomarker, we need to better understand the differential effects of age and AD by encompassing the full AD-continuum from cognitively unimpaired (CU) to dementia, including all MTL subregions with up-to-date approaches and using longitudinal designs to assess atrophy more sensitively. Age-related trajectories were estimated using best-fitted polynomials in 209 CU adults (aged 19-85). AD-related changes were investigated among amyloid-negative (Aβ-, n=46) and amyloid-positive (Aβ+, n=14) CU, Aβ+ patients with mild cognitive impairment (MCI, n=33) and AD (n=31). Nineteen MCI-to-AD converters were also compared to 34 non-converters. Relationships with cognitive functioning were evaluated in 63 Aβ+ MCI and AD patients. All participants were followed up to 47 months. MTL subregions – the anterior and posterior hippocampus (aHPC/pHPC), entorhinal cortex (ERC), Brodmann areas (BA) 35 and 36 [as perirhinal cortex (PRC) substructures], and parahippocampal cortex (PHC) – were segmented from T1-weighted MRI using a new longitudinal pipeline (LASHiS). Statistical analyses were performed using mixed models. Adult lifespan models highlighted both linear (PRC, BA35, BA36, PHC) and nonlinear (HPC, aHPC, pHPC, ERC) trajectories. Group comparisons showed reduced baseline volumes and steeper volume declines over time for most MTL subregions in Aβ+ MCI and AD patients compared to Aβ- CU, but no differences between Aβ- and Aβ+ CU or between Aβ+ MCI and AD patients (except in ERC). MCI-to-AD converters exhibited greater volume decline over time than non-converters in HPC, aHPC and pHPC. Most MTL subregions were related to episodic memory performances but not to executive functioning or speed processing. Overall, these results emphasize the benefits of studying MTL subregions to distinguish age-related changes from AD. Interestingly, MTL subregions are unequally vulnerable to aging, and those displaying nonlinear age-trajectories, while not damaged in preclinical AD (Aβ+ CU), are particularly affected from the prodromal stage (Aβ+ MCI). This volume decline in hippocampal substructures might also be informative regarding the conversion from MCI to AD-dementia. Together, these findings provide new insights into MTL alterations, which are crucial for AD-biomarkers definition.